Short Communication: Efficacy of Copxykil Against Some Pathogenic and Non-Pathogenic Microorganisms: Short Communication: Efficacy of Copxykil against Microbes - Khatoon, Tahera; Rizki, Yazdana M.; Parveen, Shahnaz; Qaimkhani, Muhammad Ishaq (Biological Sciences - PJSIR, 2009)
Efficacy of copxykil – with copper oxychloride as active ingredient – as fungicide and bactericide was evaluated against Alternaria alternata, Fusarium oxysporum, F. solani, Aspergillus flavus, A. fumigatus, A. niger and Pencillium expansum as well as against Escherichia coli, Shigella dysentriae and compared with a standard imported commercial product ‘COBOX’. The test fungicide proved to be more effective than the commercial one.